Contingent value of director identification: The role of government directors in monitoring and resource provision in an emerging economy. (7th July 2015) - Zhu, Hongjin; Yoshikawa, Toru
Abstract : Research summary: Although previous studies have explored the value of government directors, less attention has been directed at the antecedents of government directors' engagement in value‐adding activities, such as managerial monitoring and resource provision. Drawing on social identity theory, we offer a novel model that specifies how a government director's dual identifications with the focal firm, and with the government individually and interactively affect his or her governance behavior. An investigation of government directors in China shows that their identification with the focal firm enhances monitoring and resource provision, while their identification with the government affects monitoring and resource provision differently. depending on the dominance of state ownership. The synergistic/substitutable effects between the two types of identification are contingent on state ownership and governance roles. Managerial summary: This study examines how a government director's dual identities—as a government official and as a board member of a focal firm affect his or her engagement in managerial monitoring and resource provision. Using data of Chinese listed firms, we find that government directors who strongly identify with the focal firm or with the government are highly motivated to fulfill their fiduciary obligations. However, the positive effects of their identification with the government differ between state‐owned enterprises (SOEs) and non‐SOEs. The combination of the two identifications offers a further boost to monitoring in non‐SOEs, and to resource provision in both SOEs and non‐SOEs, but it acts as a disincentive to monitoring in SOEs. Copyright © 2015 John Wiley & Sons, Ltd.